GIS applications for engineering. - Gualdrón Alfonso, Diego Fernando; Universidad Pedagógica y Tecnológica de Colombia; Villate Corredor, José Julián; Universidad Pedagógica y Tecnológica de Colombia; Reyes Medina, Pedro Santiago; Universidad Pedagógica y Tecnológica de Colombia; Silva Balaguera, Andrés Leonardo; Universidad Pedagógica y Tecnológica de Colombia; Rodríguez González, Jorge Luis; Universidad Pedagógica y Tecnológica de Colombia; Daza Leguizamón, Omar Javier; Universidad Pedagógica y Tecnológica de Colombia; Vera López, Enrique; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2020)
In recent years the concern for the conservation and optimization of natural resources and the environment, as well as existing territorial problems, make it necessary to collect, process and analyze information for the development of research, which can be laborious, complex and expensive, that is why Geographic Information Systems (GIS) have acquired significant relevance when analyzing problems related to spatial information, since they allow the automation, visualization and manipulation of geographic data, becoming a fundamental tool for the decision making. GIS, besides to performing operations reliably, provide the user with information related to spatial phenomena, which has great importance in the research field, considering that a large part of the information on natural and environmental resources that is handled is linked with geographic or spatial information. This book is a compilation of research results developed during the years 2018 - 2019, focused on the applications of GIS in various areas of civil engineering.